World history demystified - Muntone, Stephanie (Demystified series, 2012)
Gives you the opportunity to learn this subject at your own pace. Master topics such as important dates; the great civilizations of Ancient Greece and Rome Empires; the scientific developments of the Ancient Egyptians; the various dynasties of China; as well as fun and interesting facts. The book helps you truly comprehend this challenging subject a without overwhelming you with complexities or mystifying jargon.